2019
DOI: 10.1002/pmh.1443
|View full text |Cite
|
Sign up to set email alerts
|

Paranoia and risk of personality disorder in the general population

Abstract: Background We hypothesized that paranoia is associated with personality disorder (PD) in the general population. Method This was a population‐based cross‐sectional survey carried out in Andalusia (Spain) using a representative sample of 4 507 participants. Paranoia was measured using the Green Paranoid Thought Scale, and risk of having a PD was screened using the Standardized Assessment of Personality Abbreviated Scale whilst borderline personality disorder (BPD) was measured with the CEPER‐III Exploratory Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Regarding the relationship between DD and personality, our findings would indicate that the prevalence of PDs is probably higher in DD patients than in the general population. This is in line with the hypothesis that specific PDs are associated with DD [24]. Notably, 81.25% of DD patients in our sample presented a co-diagnosis of PD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the relationship between DD and personality, our findings would indicate that the prevalence of PDs is probably higher in DD patients than in the general population. This is in line with the hypothesis that specific PDs are associated with DD [24]. Notably, 81.25% of DD patients in our sample presented a co-diagnosis of PD.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, having at least one PD is associated with higher psychopathological scores on affective dimensions, including floating anxiety, guilt, depression, and somatic obsessions [23]. Another study hypothesized that DD is associated with PD in the general population [24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to psychotic disorders in which paranoia was based upon victimization, suspicion, and threat of harm, in autism-spectrum disorders, paranoia was based less upon these but more so upon social cynicism[ 68 ]. Yet, certain (developing) personality accentuations or disorders that involve paranoia and suspiciousness, in particular paranoid, schizotypal and borderline personality[ 69 , 70 ], might have contributed our findings. However, for the ongoing personality development in this age group, we had not assessed these in our study on children and adolescents.…”
Section: Discussionmentioning
confidence: 85%
“…Although NDP decreased significantly for both groups over follow-up assessments, the BPD group endorsed NDP at more than twice the rate (43.3%) of those with other PDs (20.7%) 16 years later. More recent work has found that although paranoia is not uncommon in other personality disorders, it is particularly associated with risk for BPD [22]. Moreover, paranoia is more prevalent and severe in BPD compared to dysthymia [23] and even schizophrenia [19].…”
Section: Paranoia and Mistrust Beliefsmentioning
confidence: 99%